Sorghum as Sustainable Ṭayyib Food: A Study on Local Consumption Strategies and the Implementation of Maqāṣid al-Sharī‘ah in Beber Subdistrict - Vidiati, Cory; Fernando, Ardi; Dapiah; Selasi, Dini; Lubaba, Abu; Sundayana, Aditia; Sahaya, Aini (Ecopreneur : Jurnal Ekonomi dan Bisnis Islam, 2025)
Food security in Indonesia remains fragile due to heavy dependence on rice and wheat as staple foods. This reliance creates structural risks when domestic output is insufficient or global supply chains are disrupted. Diversifying local food sources is therefore essential to strengthening national resilience. This study examines strategies to enhance sorghum consumption in Beber Subdistrict, Cirebon Regency, positioning it as ṭayyib food within the framework of maqāṣid al-sharī‘ah. A qualitative descriptive method was applied, using secondary data from journals, international reports, government documents, and local publications. Thematic analysis focused on three themes: sorghum’s potential, local consumption strategies, and the role of policy and institutions. Findings show that bioguma sorghum in Beber yields 10–16 tons per harvest with up to three harvests annually, far above the national average. This productivity provides economic opportunities through processing into flour, noodles, and healthy snacks. Challenges remain, including limited processing facilities, low nutritional awareness, and weak village institutions. Promoting sorghum as ṭayyib food supports hifz al-nafs (protection of life), hifz al-mal (protection of wealth), and imārat al-ardh (stewardship of the earth). Integrated, community-based strategies and multi-stakeholder collaboration could position Beber as a replicable model of Islamic and sustainable local food security.